Mechanical Study of a Single-Cylinder High-Pressure Steam Engine with a Corliss Valve Gear Using Finite Element Method - José Ignacio Rojas-Sola; Santiago Sánchez-García (Applied Sciences)
This investigation analyzes the design integrity from a mechanical engineering perspective of a single-cylinder high-pressure steam engine with a Corliss valve gear designed by Arnold Throp. This concerns a double-acting steam engine that incorporates a steam distribution system using a Corliss valve gear, whose blueprints were published in the Model Engineer magazine in 1982. This is a complex historical invention given the high number of components (120) that constitute it, and for which no information exists regarding its operating conditions. Once the 3D CAD model of the same was obtained, and given that no physical model exists to subject to testing, a linear static analysis was performed at two critical positions (top dead center and bottom dead center), determining the maximum gauge pressure at the steam inlet (working pressure), such that the minimum safety factor is within an optimal range with values between 2 and 4. Said linear static analysis was performed using the stress analysis module of Autodesk Inventor Professional 2024, applying the finite element method. The results obtained confirm that the optimal range of working pressures is between 4.1 and 7.8 MPa.